مسلم فکری اور تاریخی شعور کا شاعر منظر بھوپالی( معجزہ اور حاصل کے تناظر میں ) - Dr. Farhana Qazi; Dr. Antal Zia; Dr. Anwar Ali (Khayaban - خیابان, 2022)
Manzar Bhopali is a renowned contemporary name of modern era in a field of Ghazal(A lyrical genre of Urdu Poetry).He belongs to a Muslim family of Bhopal India. In his poetry he shows a clear sence of Muslim religoues and caltural thought as well as civilizational thought. In the following article the researcher has tried to discuss this very aspect of his poetry in a brief way